Electromyographic bridge for promoting the recovery of hand movements in subacute stroke patients: A randomized controlled trial - Yu-Xuan Zhou; Yang Xia; Jia Huang; Hai-Peng Wang; Xue-Liang Bao; Zheng-Yang Bi; Xiao-Bing Chen; Yu-Jie Gao; Xiao-Ying Lü; Zhi-Gong Wang (Medical Journals Sweden, 2017)
Objective: The electromyographic bridge (EMGB) detects surface electromyographic signals from a non-paretic limb. It then generates electric pulse trains according to the electromyographic time domain features, which can be used to stimulate a paralysed or paretic limb in real time. This strategy can be used for the contralateral control of neuromuscular electrical stimulation (NMES) to improve motor function after stroke. The aim of this study was to compare the treat-ment effects of EMGB vs cyclic NMES on wrist and finger impairments in subacute stroke patients. Methods: A total of 42 hemiplegic patients within 6 months of their cerebrovascular accidents were randomly assigned to 4-week treatments with EMGB or cyclic NMES. Each group underwent a standard rehabilitation programme and 10 sessions per week of hand training with EMGB or cyclic NMES. Outcome measures were: Brunnstrom stage, upper extremity components of the Fugl-Meyer Assessment, Motor Status Scale, voluntary surface electromyographic ratio and active range of motion of the wrist and finger joints. Results: The EMGB group showed significantly greater improvements than the cyclic NMES group on the following measures: Brunnstrom stages for the hand, upper extremity - Fugl-Meyer Assessment, Motor Status Scale, and the voluntary surface electromyographic ratio of wrist and finger extensors. Eleven and 4 participants of the EMGB group who had no active wrist and finger movements, respectively, at the start of the treatment could perform measurable wrist and finger extensions after EMGB training. The corresponding numbers in the cyclic NMES group were only 4 and 1. Conclusion: In the present group of subacute stroke patients, the results favour EMGB over cyclic NMES for augmenting the recovery of volitional wrist and finger motion.